Advances in manufacturing technology VIII : proceedings of the Tenth National Conference on Manufacturing Research, Loughborough University of Technology, 5-7 September 1994 /: proceedings of the Tenth National Conference on Manufacturing Research, Loughborough University of Technology, 5-7 September 1994. (2014) - Unknown
No abstract available